Impact of Behavioral Interventions on Patient Activation in Adults with Hypertension: A Systematic Review and Meta-Analysis - Adnan Innab PhD, REM, MSN, BSN, RN; Ali Kerari PhD, RN (SAGE Publishing, 2022)
Introduction: Behavioral interventions assist patients in maintaining optimal self-management of their health, especially in those at risk of certain conditions. Little is known about the effects of self-management interventions on patient activation in adults with hypertension. Therefore, this systematic review and meta-analysis aimed to evaluate how self-management strategies affect changes in activation levels in adults with hypertension. Methods: We searched online databases: PubMed, CINAHL, and Cochrane Central Register of Controlled Trials for studies published between January 2004 and May 2021. We included randomized controlled trials that assessed the effects of self-management interventions on patient activation in adults with hypertension and reported patient activation using the patient activation measure (PAM). Results: 4 Four studies (N = 1415 participants) met the inclusion criteria. In adults with hypertension, self-management interventions improved patient activation with moderate strength of evidence. A community-based self-management program, motivational interviewing strategies, and home-based patient-activated care were associated with better PAM scores than usual care. Conclusion: Our findings reinforce the need for healthcare providers to incorporate these interventions into primary care to support the adoption of recommended hypertension self-management behaviors. Future studies must focus on tailoring support to the patient's level of activation in hypertension self-management.